Managing Data Sovereignty: An Organizational Competence for Successful Open Value Creation - Lukas Moschko; Vera Blazevic; Frank T. Piller (R&D Management, 2024)
Managing big data benefits organizations via efficient and effective data-driven decision making, productivity gains, customization potential, or innovation opportunities. Data-driven innovation opportunities are particularly valuable in open value creation (OVC), that is, the collaboration of independent stakeholders who open their boundaries to share data and knowledge to jointly create value they could not have achieved in isolation. At the same time, however, incumbents often struggle with the implementation of data sharing in the broader stakeholder ecosystem. In this exploratory study, based on an abductive qualitative study with 27 expert interviews and three industry roundtables with 19 experts, we explore how the concept of organizational data sovereignty could serve as an organizational competency to address the data challenges for OVC. Using the strategy-as-practice framework, we define organizational data sovereignty as the self-determined and intentional exercise of control over an organization's data assets and show which data sovereignty practices, in line with practitioner and praxis conditions, support inter-organizational sharing and management of big data in OVC. Specifically, we identify key practices for implementing data sovereignty, such as constituting the special value of data and establishing a consistent value assessment for data. When designed and applied in the right organizational framework that allows for openness, agility, and interdisciplinarity, they enable industrial enterprises to realize the potential of OVC.
Keywords: 650; data driven value creation; data sovereignty; industrial incumbents; open value creation; strategy-as-practice